Comparative Study of Adjuvant Temozolomide Six Cycles Versus Extended 12 Cycles in Newly Diagnosed Glioblastoma Multiforme - Bhandari, Menal (J Clin Diagn Res, 2017)
INTRODUCTION: Studies have shown promising survival with the use of Extended Temozolomide (E-TMZ) as compared to Conventional six cycles of Temozolomide (C-TMZ) in malignant gliomas; however, the reports are mostly limited to retrospective studies with significant bias. AIM: This study assesses the impact of six versus 12 cycles of adjuvant Temozolomide (TMZ) on Overall Survival (OS) in newly diagnosed postoperative patients of Glioblastoma Multiforme (GBM). MATERIALS AND METHODS: Between January 2012 and July 2013, 40 postoperative patients of GBM between age 18-65 years and Karnofsky Performance Score (KPS) ≥70 were included. Patients were randomized to receive radiation (60 Gray in 30 fractions over six weeks) with concomitant TMZ (75 mg/m(2)/day) and adjuvant therapy with either six (C-TMZ arm) or 12 cycles (E-TMZ arm) of TMZ (150-200 mg/m(2) for five days, repeated four weekly). Twenty patients were treated in each arm. Toxicity was assessed using Common Terminology Criteria for Adverse Events (CTCAE) version 3.0. OS and Progression Free Survival (PFS) were calculated from the time of diagnosis. Kaplan Meier method was used for survival analysis. A p-value of <0.05 was taken as significant and SPSS version 12.0 was used for all statistical analysis. RESULTS: Median number of adjuvant TMZ cycles was six and 12 in C-TMZ and E-TMZ arm respectively. Overall, 5% and 15% patients respectively in C-TMZ and E-TMZ arm had haematological toxicity ≥ 3 in grade. Median follow up in C-TMZ and E-TMZ arm were 14.65 months and 19.85 months. Median PFS was 12.8 months and 16.8 months in C-TMZ and E-TMZ arm respectively (p=0.069). Median OS was 15.4 months vs. 23.8 months in C-TMZ and E-TMZ arm respectively (p=0.044). CONCLUSION: Our study showed that E-TMZ is well tolerated and leads to a significant increase in PFS as well as OS in newly diagnosed patients of GBM. Further prospective randomized studies are needed to validate the findings of our study.